Conselho fiscal das sociedades anônimas e o direito de fiscalização da gestão dos negócios sociais - Momo, Vera Amaral Carvalho (2016)
Supervisory Board is the body responsible for the company's supervision. It is intended to verify compliance with legal and statutory duties of directors. It also acts as an information organ to shareholders. The objective of this study is to identify if the legal rules of the functioning of the body are effective in protecting the basic right of supervision of the company business by the shareholders. We seek to understand the role of the supervisory board in the corporate context, from the point of view of the harmonization of the various social interests pursued by the legislature